Increasing Use of Morphine in Our Hospital and Cancer Pain Relief in Our Pain Clinic - TAKAHASHI, Hiroshi; MATSUMIYA, Naoki; KONDO, Tsukasa; SANADA, Katsuhiro; ASANO, Chiyoko (JOURNAL OF THE JAPANESE ASSOCIATION OF RURAL MEDICINE, 1999)
This study was performed to evaluate management of cancer pain in 322 patients who were treated in our pain clinic between January 1986 and December 1997. For this purpose, the change in the number of cancer patients and the annual morphine consumption during the period in our hospital were investigated. We found that as morphine consumption increased, the number of cancer patients visited the pain clinic decreased. Although 90% of them who visited the pain clinic underwent neural block therapy before 1996, the parcentage dropped to only 79% in 1996 and 50% in 1997. The increasing rate of morphine consumption in our hospital was on a par with the national average between 1986 and 1996. The use of adjuvant drugs did not change throughout the 12-year period. We believe the consumption of morphine is not enough. It is necessary for us to become more skilled in using narcotics for relief of cancer pain along the guidelines of the World Health Organization.